2018
DOI: 10.1038/s41598-018-26227-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved fermentation efficiency of S. cerevisiae by changing glycolytic metabolic pathways with plasma agitation

Abstract: Production of ethanol by the yeast Saccharomyces cerevisiae is a process of global importance. In these processes, productivities and yields are pushed to their maximum possible values leading to cellular stress. Transient and lasting enhancements in tolerance and performance have been obtained by genetic engineering, forced evolution, and exposure to moderate levels of chemical and/or physical stimuli, yet the drawbacks of these methods include cost, and multi-step, complex and lengthy treatment protocols. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 88 publications
2
22
0
1
Order By: Relevance
“…The experimental data confirmed that fungi were intrinsically more resistant to CAPP exposure than bacteria (Zahoranová et al 2018). Although the eukaryotic microorganisms required longer treatment time by CAPP, they were efficiently inactivated after several minute-long exposure (Itooka et al 2018;Recek et al 2018;Zahoranová et al 2018). The inactivating mechanism of filamentous fungi by CAPP resembles the one described in bacteria.…”
Section: Fungal Decontaminationsupporting
confidence: 60%
See 1 more Smart Citation
“…The experimental data confirmed that fungi were intrinsically more resistant to CAPP exposure than bacteria (Zahoranová et al 2018). Although the eukaryotic microorganisms required longer treatment time by CAPP, they were efficiently inactivated after several minute-long exposure (Itooka et al 2018;Recek et al 2018;Zahoranová et al 2018). The inactivating mechanism of filamentous fungi by CAPP resembles the one described in bacteria.…”
Section: Fungal Decontaminationsupporting
confidence: 60%
“…CAPP was successfully employed in generation of B. subtilis mutants with a 35% increased yield of recombinant alkaline α-amylase (Ma et al 2015), Schizochytrium strain with 1.8-fold increase of docosahexaenoic acid (Zhao et al 2018), and Streptomyces bingchenggensis strain with 2-fold increase of 5oxomilbemycins A3/A4 (Wang et al 2014). S. cerevisiae mutants isolated after APPJ treatment displayed changes in cell membrane structure, increase in hexokinase 2 activity, and conversion of glucose to ethanol (Recek et al 2018).…”
Section: Animal and Microbial Breedingmentioning
confidence: 99%
“…Certain changes in membrane transport may occur because of the strong interactions between the membrane molecules and the physiochemical effects of the cold plasma, such as the enrichment of highly energetic and bioreactive species in the medium surrounding the cells, as shown in Figure S4 (the typical optical emission spectra (OES) of the APCP jet). Previous studies on the APCP and cell interactions have confirmed that cell responses to the plasma effects led to the formation of pores in the cell membranes and the alteration of cell permeability toward crucial nutrients, organic molecules, and/or other particles. ,,, The typical angle-resolved XPS C 1s spectra of APCP-unstressed S. cerevisiae cells and those stressed for 3 min are shown in Figure S5.…”
Section: Resultsmentioning
confidence: 84%
“…In this study, with the nanodiamond chosen as a model nanomaterial, we chemically modify the NDs with different surface charges (strongly positive and negative), and evaluate their internalization and cytotoxicity to yeast (Saccharomyces cerevisiae) and human cells (near-normal epithelial cells; MCF-10A; and breast cancer cells, MDA-MB-468 and T47D). To further understand the potential effects of exposing cells to the complex environment on charge-dependent ND toxicity, chemo-radiative stress provided by a cold atmospheric plasma jet (as a proxy for other external or internal factors, such as UV radiation from sun, reactive oxygen species (ROS) and reactive nitrogen species (RNS) from the environment or produced by cells, as the results of oxidative stress) is then introduced . The results show that the application of such external stress can alter the sensitivity of cells to the toxicity of NDs, which were otherwise proven to be nontoxic (over the experimental dosage range) to all investigated cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Complementary to the abovementioned findings on microbial inactivation, and consistent with the possible DNA damage by plasma, atmospheric pressure plasma has been shown to be a useful tool to induce mutagenesis to generate various strains of microbes that can be used for nonplasma applications including chemical synthesis, petroleum hydrocarbon degradation, and hydrogen formation, and that can survive under high-salt conditions. [31][32][33][34][35][36] Microbial survival and strain evolution are of further relevance to the utilization of sequential combinations of plasma reactors, followed by bioreactors, for enhanced chemical degradation; in such systems, microbial resistance to plasma-generated chemical species may significantly enhance system efficiency for degrading pollutants. [37] It is well established that plasma discharges formed in argon carrier gases contacting liquid water lead to the formation of significant quantities of hydrogen peroxide.…”
mentioning
confidence: 99%